A modified approach to incorporate the Poisson’s effect in the Softened Membrane Model - Bavukkatt, Rajeevan; Sengupta, Amlan K.; Belarbi, Abdeldjelil (Journal of Structural Engineering, 2024)
The in-plane shear stress versus strain behaviour of a finite element in a wall-type reinforced concrete (RC) structure can be predicted by the Modified Compression Field Theory (MCFT) and the Softened Membrane Model (SMM). In the formulation of the SMM, the Poisson’s effect generated in a state of biaxial stresses is considered. The Poisson’s effect refers to the generation of additional tensile and compressive strains, due to the orthogonal compression and tension, respectively, developed under in-plane shear. The biaxial tensile strain is substantial and is influenced by the cracking of concrete and reduction of the tension stiffening effect from the concrete. The present research quantified the biaxial strains in RC panels with the reinforcing bars inclined at 45° to the directions of applied tension and compression, a condition similar to that in the elements of a wall under in-plane shear. The loading was sequential to formulate the biaxial tensile strain in terms of the state of stress in each material individually. Based on the stress-based formulation, an alternate model to incorporate the Poisson’s effect in the SMM is presented. The proposed formulation is validated through the prediction of the shear stress versus strain behaviour of a few panels available from the literature.